2003
DOI: 10.1021/ma021522x
|View full text |Cite
|
Sign up to set email alerts
|

Electrooptical Behavior of Liquid-Crystalline (Hydroxypropyl)cellulose/Inorganic Salt Aqueous Solutions

Abstract: The selective light reflection and turbidimetric property of concentrated aqueous solutions of (hydroxypropyl)cellulose (HPC), originating from their cholesteric mesophase structure and LCSTtype phase behavior, respectively, are much affected by coexistence of inorganic salts therein. This is ascribed to a strong dependence of both cholesteric helical pitch (P) and cloud point (T c) of the aqueous cellulosic solutions on the sort and concentration of the additive salts. By virtue of electrophoretic motility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 10 publications
(29 reference statements)
2
35
0
Order By: Relevance
“…Figure 13 . This behavior is phenomenologically parallel to that found in previous experiments [61] using conventional alkali-metallic salts and was interpreted as being primarily a result of the generation of a disproportional dislocation of CnMim + and X À as P and/or T c shifters. In fact, the ionic fluctuation gives rise to an inner gradient of electric potential in the concentrated polymer medium.…”
Section: Dynamic Control Of Chiral Nematic Pitch and Optical Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…Figure 13 . This behavior is phenomenologically parallel to that found in previous experiments [61] using conventional alkali-metallic salts and was interpreted as being primarily a result of the generation of a disproportional dislocation of CnMim + and X À as P and/or T c shifters. In fact, the ionic fluctuation gives rise to an inner gradient of electric potential in the concentrated polymer medium.…”
Section: Dynamic Control Of Chiral Nematic Pitch and Optical Propertiessupporting
confidence: 81%
“…A significant example of such functional development is the ion-mediated dynamic manipulation of cholesteric coloration and optical turbidity by using electrical stimulation of HPC lyotropics, including swollen gels [10,[61][62][63][64]. In the first demonstration [61], conventional metallic salts were employed as additive ions to shift P and/or T c . Such a dynamic concept is based on the possible electrophoretic migration of the dissociated ionic particles, as represented diagrammatically in Fig.…”
Section: Dynamic Control Of Chiral Nematic Pitch and Optical Propertiesmentioning
confidence: 99%
“…(In this study, the DS value of the HPC sample was determined on the basis of 1 H NMR data according to a method proposed by Ho et al 29 Some of the previous articles 13,17,18 reported DS¼1.8 for the same grade (Lot#5) of HPC from the same commercial origin; the value was determined by quantitative-mode solid-state 13 C NMR measurements.) 30 …”
Section: Experimental Procedures Polymer Materialsmentioning
confidence: 99%
“…17 However, there may be a certain difference between the two cases, in the process generating the disparity in cation/anion distribution. In the previous case, the electrical stimulation allows ion particles to directly migrate and localize in the lyotropic system, as the added salt would have already been completely ionized.…”
Section: Lcst-type Phase-separation Behaviormentioning
confidence: 99%
See 1 more Smart Citation